Definition of the research and innovation field of "Artificial Intelligence" and approaches to determining quality - Bernd Beckert; Henning Kroll (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2024)
In the race for international leadership in the field of artificial intelligence, China has been in first place for years - both in terms of the number of AI research contributions and of citations. Since the publication of ChatGPT at the end of 2022 at the latest, this contradicts the general impression that the main AI innovations are currently coming from the USA rather than China, as well as the general assessment that German and European research is also making important contributions to the AI development. One reason for this divergence is the fact that AI is a very heterogeneous field of research and innovation that consists of different technologies, methods and applications. A standardized definition does not yet exist. However, adequate research field definitions are essential for country comparisons based on bibliometric and patent analyses. (...) – – Im Wettlauf um die internationale Führungsrolle im Bereich "Künstliche Intelligenz" liegt China seit Jahren auf Platz 1 - und zwar sowohl im Hinblick auf die Anzahl der KI-Forschungsbeiträge als auch bei den Zitationen. Dies widerspricht spätestens seit der Veröffentlichung von ChatGPT Ende 2022 dem generellen Eindruck, dass die wesentlichen KI-Innovationen derzeit nicht aus China, sondern aus den USA kommen sowie der allgemeinen Einschätzung, dass auch die deutsche und europäische Forschung wichtige Beiträge zur KI-Entwicklung liefern. Ein Grund für dieses Auseinanderklaf- fen ist die Tatsache, dass KI ein sehr heterogenes Forschungs- und Innovationsfeld ist, das aus verschiedenen Technologien, Methoden und Anwendungen besteht. Eine einheitliche Definition gibt es bisher nicht. Für Ländervergleiche, die auf bibliometrischen Analysen und auf Patentauswertungen basieren, sind adäquate Forschungsfelddefinitionen aber essentiell. (...)
Keywords: 330; Definition of artificial intelligence; bibliometric delineation; advanced AI; country comparisons; AI models; AI research; application of AI; quantitative analysis of different methods to identify AI-relevant research